2014
DOI: 10.1080/21642850.2013.869175
|View full text |Cite
|
Sign up to set email alerts
|

Perceived behavioral control, intention to get vaccinated, and usage of online information about the human papillomavirus vaccine

Abstract: Objective: Human papillomavirus (HPV) and the HPV vaccine have been examined through multiple lenses over the past several years, though there is little work examining the role of perceived behavioral control (PBC) and its impact on potential recipients retrieving, understanding, and using online information with regard to the vaccine. Method: This study used survey data to examine the role of PBC as a moderator between attitudes and intention, and subjective norms (SN) and intention to get the HPV vaccine; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 34 publications
6
27
1
Order By: Relevance
“…Results from two surveys provided correlational associations between receiving information about HPV and HPV vaccination via social media and positive beliefs about the vaccine and desire to search for more information. 53,55 In focus groups with adolescents in North Carolina, they indicated that they would be generally interested in receiving information about HPV and the HPV vaccine via social media, as long as the messages were interesting and credible. 64 College students in Hawaii also indicated in focus groups that they felt that social media (i.e., Facebook) could be a good platform to share accurate and useful information about HPV and the HPV vaccine but that they would not feel comfortable sharing information with their friends until they felt more knowledgeable about the topics and could personalize the message themselves to make it relevant to their friends.…”
Section: Social Media Use For Information and Discussion About Hpv Anmentioning
confidence: 99%
“…Results from two surveys provided correlational associations between receiving information about HPV and HPV vaccination via social media and positive beliefs about the vaccine and desire to search for more information. 53,55 In focus groups with adolescents in North Carolina, they indicated that they would be generally interested in receiving information about HPV and the HPV vaccine via social media, as long as the messages were interesting and credible. 64 College students in Hawaii also indicated in focus groups that they felt that social media (i.e., Facebook) could be a good platform to share accurate and useful information about HPV and the HPV vaccine but that they would not feel comfortable sharing information with their friends until they felt more knowledgeable about the topics and could personalize the message themselves to make it relevant to their friends.…”
Section: Social Media Use For Information and Discussion About Hpv Anmentioning
confidence: 99%
“…Twitter is an important source of information regarding HPV and vaccine hesitancy, 32 48 49 and several studies have examined the representation of HPV vaccines on Twitter. 33 43 50–54 Though many of these studies analyse a limited number of HPV-related tweets, a few have used data mining and machine learning techniques to analyse a large number of tweets. 51 52 54 55 However, no research has conducted an international comparison to evaluate and compare how vaccination concerns are expressed across countries.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, additional interventions are needed to support and provide young people with HPV vaccine information. Innovative interventions supported by health-care professionals and tailored to meet young people’s information-seeking behaviors, such as online and social media should be explored (Britt, Hatten, & Chappuis, 2014). Increasing the perception of HPV vaccine as a preventive measure, much like wearing a seat belt or getting a flu shot, may be an important message to increase mandate support among parents and young people.…”
Section: Discussionmentioning
confidence: 99%